2018
DOI: 10.1080/24740527.2017.1422115
|View full text |Cite
|
Sign up to set email alerts
|

Pain experiences of adults with osteogenesis imperfecta: An integrative review

Abstract: Background: Pain is a common symptom of osteogenesis imperfecta (OI) among children and adolescents. However, little is currently known of the pain experiences of adults with OI. Aims: The aims of this study were to critically appraise the studies assessing OI pain, to synthesize the pain experiences of adults with OI, and to compare the adult OI pain experiences to childhood. Methods: An integrative review was conducted. Five electronic bibliographic databases were searched. Published quantitative, qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…This is comparable with observations of other studies, ( 15,21 ) and has also been observed in review studies for pain in children with OI. ( 22 )…”
Section: Discussionmentioning
confidence: 99%
“…This is comparable with observations of other studies, ( 15,21 ) and has also been observed in review studies for pain in children with OI. ( 22 )…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a high incidence of chronic pain has been detected in this collective, [11,12] which disrupts everyday activities and is found to be resistant to surgical, pharmacological and nonpharmacological intervention. [13] The International Association for the Study of Pain (IASP) defines pain as "An unpleasant sensory and emotional experience associated with, or resembling that associated with, actual or potential tissue damage," [14] mentioning in its "key notes" the subjective nature of this experience, and how this is influenced by psychological and learned factors. Chronic pain, in more specific terms, is that which persists beyond the healing period (generally more than 3 to 6 months) and, therefore, has lost its adaptive value.…”
Section: Introductionmentioning
confidence: 99%
“…Pain is a highly common driver of reduced quality of life across rare, musculoskeletal diseases [4,21,32]. Prominent and more accessible features of musculoskeletal disease such as skeletal deformities and lesions, or muscle atrophy and weakness garner extensive clinical and research attention, whereas the neurobiological cause(s) of pain have been less well-studied in this clinical domain.…”
Section: Introductionmentioning
confidence: 99%